2015
DOI: 10.1016/j.jfoodeng.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Production of milk foams by steam injection: The effects of steam pressure and nozzle design

Abstract: Please cite this article as: Jimenez-Junca, C., Sher, A., Gumy, J-C., Niranjan, K., Production of milk foams by steam injection: the effects of steam pressure and nozzle design, Journal of Food Engineering (2015), doi: http://dx. AbstractFoam properties depend on the physico-chemical characteristics of the continuous phase, the method of production and process conditions employed; however the preparation of barista-style milk foams in coffee shops by injection of steam uses milk as its main ingredient which li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Kondisi ini bisa terjadi dikarenakan semakin tinggi suhu frothing maka semakin lama proses injeksi uap dan semakin lama proses aerasi. Volume buih yang terbentuk dengan metode injeksi uap sangat berkaitan dengan jumlah udara yang diinjeksikan dan kemampuan protein di permukaan buih dalam menjaga udara yang terperangkap (Jimenez-Junca et al, 2015). Karena itu, semakin lama waktu frothing maka buih yang terbentuk akan semakin banyak.…”
Section: Gambar 3 Volume Buih Susu Pada Beberapa Suhu Frothingunclassified
“…Kondisi ini bisa terjadi dikarenakan semakin tinggi suhu frothing maka semakin lama proses injeksi uap dan semakin lama proses aerasi. Volume buih yang terbentuk dengan metode injeksi uap sangat berkaitan dengan jumlah udara yang diinjeksikan dan kemampuan protein di permukaan buih dalam menjaga udara yang terperangkap (Jimenez-Junca et al, 2015). Karena itu, semakin lama waktu frothing maka buih yang terbentuk akan semakin banyak.…”
Section: Gambar 3 Volume Buih Susu Pada Beberapa Suhu Frothingunclassified
“…Due to the nature of the steam injection foaming method, which is decided by the practical experience of a steaming operator, any changes in foaming conditions (e.g., initial milk temperature, position of steam wand, type of steam injector, foaming time, final foaming temperature, and way to handle the milk container) result in the production of foam with different properties. 4 The foaming properties of milk are also dependent on many other factors, ranging from source, quality, and composition of milk to milk processing and storage conditions. 5 Although a substantial number of studies on the foaming process of milk have been reported, controlling the foaming process of milk on demand is still a challenge to the dairy researchers and the industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the former type, the mixture of liquid and hydrogen gas passes down a fixed bed of catalyst, where bubbles are generated by the collision between the fluids and catalyst particles, while in the latter type, hydrogen-rich recycled gas is delivered as bubbles through a mixture of oil and catalyst particles, where bubbles are generated due to the velocity gradient between the gas and liquid phase. In both types of reactors, it is difficult to generate small bubbles of hydrogen gas because the gas-liquid mixture or gas emerges from ejectors or channels that have a low pressure drop between 1 and 3 bar [7,8]. Measurement of the air bubble size ejected from a channel into water shows that it varies from 0.3 to 1.6 mm from channels [9] or 0.5 to 3 mm from ejectors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the air bubble size ejected from a channel into water shows that it varies from 0.3 to 1.6 mm from channels [9] or 0.5 to 3 mm from ejectors [10]. With such a low pressure drop, it is difficult to generate a high shear rate between gaseous and liquid phases to induce bubble breakup to form small gas bubbles [7,8]. Moreover, large-sized bubbles easily rise to the liquid surface, which consequently lowers the holdup of bubbles in the liquid phase [11], whereas high gas holdup or high gas dispersion in the liquid phase is of importance to improve the kinetics of the gas-liquid reactions [12].…”
Section: Introductionmentioning
confidence: 99%